Job Safety Analysis Sebagai Upaya Pengendalian Resiko Kecelakaan Kerja - Misbakhul Munir (Jurnal Universal Technic, 2023)
PT Wahana Kasih Mulia is a PT engaged in the manufacture of baby equipment. In the production process, which uses a lot of machines and heavy equipment such as cutting machines, pressing machines, and sewing machines, there are potentials and hazards that can cause accidents to operators/employees. This research was conducted by measuring failure in every activity in PT. Wahana Kasih Mulia, measurements were made on every machine in the factory area. Data processing is done by calculating the failure rate, failure effect, incident rate, then determining the detection rate and calculating the RPN value to determine which priority should be taken using the Job Safety Analysis method. Research results There are work accidents at PT. Rides of Noble Love, Hands pierced by needles, Cuts by cutting machines, hands exposed Penulis 1./ Job Safety Analysis Sebagai Upaya Pengendalian Resiko Kecelakaan Kerja., Januari 2023 pp. 1-4 to electric presses, Eyes exposed to dacron dust, Fall of piles of finished materials, skin irritation from dacron dust, Breathing problems due to dirty dust. Proposed improvements that can be given are adding some personal protective equipment that is appropriate to the work and factory environment, operators must use safety glasses, face shields, mask earmuffs, safety gloves, safety shoes.